New Interpretations and Adaptations of Shakespeare’s Plays in Japan from 2020 to 2023 - Kawai, Shoichiro (Multicultural Shakespeare: Translation, Appropriation and Performance, 2024)
This essay examines some notable Shakespearean productions and adaptations in Japan from 2020 to 2023. The main focus is on a Hamlet production by Mansai Nomura, a Kyogen performer, in March 2023; it was an amalgamation of the traditional Japanese theatres, such as Kyogen, Nô, Kabuki, and Bunraku. Mansai’s aspiration to produce Hamlet, utilizing all the elements of traditional Japanese art forms, began twenty years ago, when he played Hamlet in Jonathan Kent’s production in London and in Tokyo. He re-examined the text and offered a completely new interpretation of a scene, giving the play a fresh dimension. Moreover, this essay examines other recent Shakespeare productions and adaptations, including my two new plays based on Shakespeare, as well as Kôki Mitani’s Thirteen Vassals of Kamakura Shogun, a serial historical TV drama, broadcast by NHK (Japan’s version of the BBC).